International Forum: The Turkish perspective on apheresis activity: The Turkish apheresis registry report - Ozatli, Duzgun; Giden, Asli Odabasi; Erkurt, Mehmet Ali; Korkmaz, Serdal; Basci, Semih; Ulas, Turgay; Altuntas, Fevzi (Pergamon-Elsevier Science Ltd, 2023)
Therapeutic apheresis is an extracorporeal treatment that selectively removes abnormal cells or harmful sub-stances in the blood that are associated with or cause certain diseases. During the last decades the application of therapeutic apheresis has expanded to a broad spectrum of hematological and non-hematological diseases due to various studies on the clinical efficacy of this procedure. In this context there are more than 30 centers per-forming therapeutic apheresis and registered in the apheresis database in Turkey. Herein, we, The Turkish Apheresis Registry, aimed to analyze some key articles published so far from Turkey regarding the use of apheresis for various indications.
Keywords: Turkey; Apheresis; Activity; Registry; Report